Guidelines for dopant selection in Cu catalysts to promote the electrochemical CO2 reduction reaction for ethylene production - Kim Dogyeong; Ka Seohyeon; Han Man Ho; Kim Woong; Yu Seung-Ho; Choi Jae-Young; Chae Keun Hwa; Oh Hyung-Suk; Lee Woong Hee (Elsevier BV, 2025)
To develop an efficient electrochemical CO2 reduction reaction (CO2RR) for the production of C2 chemicals, improvements in the Cu catalyst are necessary. Doping is widely used for catalyst enhancement; however, only a few elements have been examined. This study proposes guidelines for the selection of Cu catalyst dopants to promote ethylene production. It was hypothesized that the dopant chemical state highly influences the CO2RR catalytic activity. In the case of dopants possessing a standard reduction potential within the CO2RR potential region (e.g., Mn and Ni), low Faradaic efficiency (FE) toward ethylene production was obtained owing to the presence of a metallic dopant (10.7% for Ni dopant). In contrast, a low standard reduction potential led to a stable high oxidation state for the dopant, yielding abundant Cuδ+ species with modified electronic structures and enhancing the CO2RR catalytic activity for ethylene production (42.1% for Hf dopant). We expected that a dopant with a low standard reduction potential is difficult to reduce, which leads to a stable Cu？O？X bond and induces a stable Cuδ+ species. Our study provides insights into how to select dopant for various catalyst to enhance CO2RR catalytic activity.